Multipurpose prevention technologies for the prevention of unintended pregnancy, HIV, and other sexually transmitted infections: regulatory pathways and challenges - Donaldson, Logan; Schaefer, Robin; Alhakimi, Sarah; Akulu, Ruth; Palanee-Phillips, Thesla; Young Holt, Bethany; Miller, Veronica (Frontiers in Reproductive Health, 2025)
Multipurpose prevention technologies (MPTs) are multi-indication products commonly focusing on the prevention of unintended pregnancy, HIV, and/or other sexually transmitted infections (STIs). MPTs have the potential to simplify product use and service delivery with reduced clinic visits, thus supporting improved product uptake, effective use, and cost-effectiveness. MPTs are complex products that typically include multiple active pharmaceutical ingredients (APIs), with two or more indications, and often use a device to deliver these APIs. These complexities create challenges when seeking regulatory approval. Products with previously approved APIs may be able to rely on bioequivalence (BE) studies, but still face challenges in formulation variation, drug-drug interaction, and fulfilling strict standards. MPTs that use new APIs and devices cannot rely on BE studies for approval and thus face further uncertainty, including clinical trial design for products with multiple indications and outcomes of interest. Efficacious standards of care for HIV prevention and contraception also necessitate active-control designs for registrational clinical trials, thus innovative trial designs may be needed. Compounding these challenges are special regulatory requirements for combination products, in addition to standards applied to individual API and device. Possible approval pathways for combination products exist within the US Food and Drug Administration and other global regulatory authorities, but their complexities and challenges are untested for MPTs. They are highlighted in this article to raise awareness around regulatory pathways for MPTs. In Sub-Saharan Africa, women of reproductive age are the largest percentage of new HIV infections. This, in combination with considerable rates of unintended pregnancy and rising sexually transmitted infection (STI) rates, highlights the need for products that address these complex sexual and reproductive health needs. Multipurpose prevention technologies (MPTs) commonly focus on the prevention of unintended pregnancy, HIV, and/or other STIs in one product. MPTs combine the use of multiple pharmaceutical drugs and often a medical device to address these interrelated challenges. This creates complications in the design of studies for MPTs and in understanding the process of approval from regulatory authorities. Regulatory authorities are responsible for ensuring the safety and effectiveness of health products, and in MPTs this is complicated by targeting the prevention of multiple indications, with differing study designs and challenges, in one product. There are mechanisms in place at some regulatory authorities to evaluate MPTs, but these pathways are untested by product developers and regulatory authorities alike. Some of these pathways are highlighted below. Collaboration between diverse stakeholders like regulators, academics, product developers, and community members is necessary to build consensus on the best steps to address these challenges. MPTs are a potential tool to successfully prevent interrelated sexual and reproductive health concerns, but regulatory challenges must be addressed for safe and effective products to reach those who need them most.